Peptide Modified ZnO Nanoparticles as Gas Sensors Array for Volatile Organic Compounds (VOCs) - Mascini, Marcello; Gaggiotti, Sara; Della Pelle, Flavio; Di Natale, Corrado; Qakala, Sinazo; Iwuoha, Emmanuel; Pittia, Paola; Compagnone, Dario (Frontiers in Chemistry, 2018)
In this work a peptide based gas sensor array based of ZnO nanoparticles (ZnONPs) has been realized. Four different pentapeptides molecularly modelled for alcohols and esters having cysteine as a common spacer have been immobilized onto ZnONPs. ZnONPs have been morphologically and spectroscopically characterized. Modified nanoparticles have been then deposited onto quartz crystal microbalances (QCMs) and used as gas sensors with nitrogen as carrier gas. Analysis of the pure compounds modelled demonstrated a nice fitting of modelling with real data. The peptide based ZnONPs had very low sensitivity to water, compared to previously studied AuNPs peptide based gas sensors allowing the use of the array on samples with high water content. Real samples of fruit juices have been assayed; stability of the signal, good repeatability and discrimination ability of the array was achieved.